Utilização de veículos aéreos não tripulados e desenvolvimento de um sistema de aquisição de dados de baixo custo para sondagem atmosférica - Hackbart, Theo (2008)
This work describes the construction of an unmanned aerial vehicle (UAV) with electrical propulsion and instrumentation in order to obtain the vertical and horizontal profiles by measuring temperature, pressure, and GPS location, in surface atmosphere layer between two heterogeneous surfaces near terrain. Using embedded electronic, one developed and built a small platform with approximately 50 grams in order to collect and acquire meteorological data. The electronic circuit is based on a PIC microcontroller with pressure and temperature sensors, and GPS. After capturing aerosondes data, the first analysis was done. By using these data, surface boundary layer structure compatible with general concepts in the literature were identified. It was also identified some details of closed structures to the frontier which separates the heterogeneous region of landcover. According to several researches aiming at sdudying different alternatives to obtaining the data, one demonstrated through this experimental that small UAVs can be very useful for agrometheorology and metheorology researches because they provide the atmospheric sounding to be performed in places where the access is difficult. Furthermore, they present a low cost.